Colocalized nevus depigmentosus and lentigines - Prashansa Jaiswal; Sundeep Chowdhry; Paschal D' Souza (Our Dermatology Online, 2016)
Nevus depigmentosus (ND)is classically defined as a congenital nonprogressive hypopigmented macule, stable in size and distribution. A 17 year girl presented with hypopigmented patch with indented borders, present on the right side of face and neck since 3 years of age. Later on at the age of 5, numerous hyperpigmented punctiform spots appeared exclusively on the hyperpigmented area. On sun exposure, the hypopigmented area neither reddened nor burnt. On diascopy the margin of the hypopigmented lesion remained delineated. The dermoscopic examination showed 1-4 millimeters sized hyperpigmented lesions with a barely visible pseudonet, leading to the final diagnosis of colocalized nevus depigmentosus and lentigines.